The hospitalization burden of inflammatory bowel disease in a southwestern highland region of China: a territory-wide study from 2015 to 2020 - Tao, Yan; Li, Maojuan; Gao, Huabin; Sun, Yang; Zhang, Fengrui; Wu, Jing; Liang, Hao; He, Liping; Gong, Min; Niu, Junkun; Miao, Yinglei (Frontiers in Medicine, 2024)
Background Yunnan, a southwest highland and newly industrialized region of China, has an unknown hospitalization burden of inflammatory bowel disease (IBD). The study was conducted to explore territorial hospitalization burden of IBD. Methods The formatted medical records of patients with IBD were collected from a territory-wide database in Yunnan Province, China, from 2015 to 2020. General characteristics of the study population were reported using descriptive statistics. To evaluate the length of stay, hospitalization costs, surgery, complications, and trends in patients with inflammatory bowel disease. The logistic regression analysis was established to explore the factors affecting the hospitalization costs. Results A total of 12,174 records from 8192 patients were included. The annual hospitalization cost of IBD in Yunnan Province increased significantly from 2015 to 2020. From 2015 to 2020, the regional hospitalization burden of IBD increased, but it represented a decline in cost per hospitalization (r = −0.024, P = 0.008) and the length of stay (r = −0.098, P < 0.001). Surgery rates for hospitalized patients with Crohn’s disease (CD) did not decrease (r = −0.002, P = 0.932), and even increased for patients with ulcerative colitis (UC) (r = 0.03, P = 0.002). The costs per hospitalization were $ 827.49 (540.11–1295.50) for UC and $ 1057.03 (644.26–1888.78) for CD. Among the identifiable cost items during the period, drug costs accounted for the highest proportion, accounting for 33% and 37.30% in patients with UC and CD, respectively. Surgical intervention [OR 4.87 (3.75–6.31), P < 0.001], comorbidities [OR 1.72 (1.52–1.94), P < 0.001], complications [OR 1.53 (1.32–1.78), P < 0.001], and endoscopy [OR 2.06 (1.86–2.28), P < 0.001] were predictor of high hospitalization costs. Conclusion The increasing burden of IBD is noteworthy a newly industrialized region of China. Interventions targeting surgery, complications, and comorbidities may be effective means of controlling the increasing hospitalization costs of IBD in the regions.